DIGITAL TRANSFORMATION OF THE MEDICAL EDUCATION - Antoan Shotarov (Peytchinski Publishing, 2023)
Introduction: Digital transformation has drastically changed nearly every field of human life in the last couple of years. Education is not an exception. For many years changes in education have been happening at a very slow pace, but in the 21stcentury, this has changed. Some of the most important shifts in the field of medical education are related to the inclusion of AI and VR in the training of students. Aim: The article aims to analyze some of the most important effects that digital transformation has on medical education. Material and methods: The author used theoretical and practical scientific methods. Important and impactful articles related to the topic are analyzed. Results: The results of the research undoubtedly show the great importance that innovative techniques, methods, and tools, created thanks to the digital transformation, have on medical education. Conclusion: Medical students could benefit vastly from the inclusion of AI and VR in their curriculum. Thus, they will not only be eased in their daily work when they become doctors but they will be ready for the upcoming changes in the medical field as well.